2021
DOI: 10.1590/1981-22562020023.200320
|View full text |Cite
|
Sign up to set email alerts
|

Violência contra a pessoa idosa no município de Campinas, São Paulo, nos últimos 11 anos: uma análise temporal

Abstract: Resumo Objetivo Analisar as notificações dos casos de violência contra a pessoa idosa, no período de 2009 a 2019, através de dados obtidos no Sistema de Notificação de Violência (SISNOV) no município de Campinas, Estado de São Paulo, Brasil. Método Trata-se de uma pesquisa epidemiológica de abordagem quantitativa, descritiva e tendência temporal. Para as análises das notificações seguiu-se a observação das informações de acordo com as variáveis sociodemográficas, característica da violência e de seu agress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 18 publications
1
3
0
10
Order By: Relevance
“…In Brazil, violence against women is a serious social phenomenon that needs structural confrontation and the involvement of the entire society. Studies show that older women aged between 60-69 years, widows, white race/color and with a low level of education make up the highest percentage of cases of violence against older people 8,22,32 , corroborating the results of this research.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In Brazil, violence against women is a serious social phenomenon that needs structural confrontation and the involvement of the entire society. Studies show that older women aged between 60-69 years, widows, white race/color and with a low level of education make up the highest percentage of cases of violence against older people 8,22,32 , corroborating the results of this research.…”
Section: Discussionsupporting
confidence: 87%
“…Research shows that the prevalence of domestic violence against older people is higher than in other contexts, related, in most cases, to dependence on family care, low social conditions and time spent at home after retirement [6][7][8] . Poltronieri et al 9 state that violence against older people leads to increased morbidity and mortality and institutionalization, in addition to prolonged hospitalization; they generate serious consequences in terms of mental health and family and social relationships.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the role of the primary healthcare system is important, comprising the Basic Health Units (UBS) and the Family Health Care Strategy (ESF). This support network can, through closer contact between professionals and users, detect and deal with situations of family violence, particularly among the more vulnerable members of society, thanks to the ready access to care delivered under this healthcare model 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies analyzing the profile of VAE notifications in Brazil are, for the most part, restricted to the period before the COVID-19 pandemic. Eleven studies on the subject were identified, conducted in different regions of the country: three addressed notifications made nationwide, 7 , 9 , 10 one was conducted in the states of the Southern region, 11 two were conducted using data from the state of Rio Grande do Sul, 12 , 13 one was conducted in the state of Espírito Santo, 14 two involved notifications in the city of São Paulo City, 15 , 16 one in the city of Campinas 17 and one using data from the state of Pernambuco. 18 The completeness of the fields of the notification form for violence against the elderly was not assessed in these studies.…”
Section: Introductionmentioning
confidence: 99%